Is Precision Therapy in Infantile-Onset Epileptic Encephalopathies Still Too Far to Call Upon? - Raffaele Falsaperla; Vincenzo Sortino; Piero Pavone (Applied Sciences)
Epileptic and developmental encephalopathies (EDEs) are a group of severe, genetically various neurological conditions characterized by early-onset seizures and developmental impairments. Recent advances in molecular genetics and diagnostic tools have led to the development of precision therapies, aiming to address the deep causes of these disorders. Examples, such as pyridoxine for pyridoxine-dependent epilepsy and the ketogenic diet for GLUT1 deficiency syndrome illustrate the potential of presumed tailored treatments. However, challenges persist, as current therapies often fail to fully mitigate neurodevelopmental impairments. Moreover, traditional phenotype-based management strategies, while effective for seizure control, do not address the root causes of these disorders, underscoring the limitations of existing approaches. This article explores the evolving landscape of precision medicine in EDEs, emphasizing the importance of genetic insights in therapy design and the need for a multidisciplinary approach. It also highlights the barriers to widespread implementation, including diagnostic delays, accessibility, and a lack of robust clinical evidence. To fully realize the potential of precision therapies, comprehensive genetic integration, innovation in treatment, and global collaboration are essential. The future of EDE management lies in therapies that not only control symptoms but also correct genetic and molecular defects, offering a more effective, individualized approach to care.